Adaptive strategies to platoon merging with vehicle engine uncertainty. Issue 2 (2020) - Jain, Vishrut; Liu, Di; Baldi, Simone
Abstract: While several synchronization-based protocols have been provided for formation-keeping of cooperative vehicles, the problem of synchronized merging is more challenging. Challenges associated to the merging scenario include the need for establishing bidirectional interaction (in place of unidirectional look-ahead interaction), and the need for considering different engine dynamics (in place of homogeneous engine dynamics). This work shows how such challenges can be tackled via a newly proposed strategy based on adaptive control with bidirectional error: the adaptive control framework autonomously adapts to different engine dynamics, while the bidirectional error seamlessly allows the vehicle that wants to merge to interact with both the front and the rear vehicles, in a similar way as humans do.